European and International Perspectives on Benefit-Cost Analysis: Symposium Introduction. Issue 1 (2021) - Florio, Massimo
Abstract: The idea of assessing the costs and benefits of public and private projects is not new to Europe, dating back to studies at the Ecole des Ponts et Chaussees (Paris) in the XIX century. Later on, in the last century, Benefit-Cost Analysis (BCA) in its current form has been more extensively used in the United States than in Europe. In the last two decades, however, there has been a rapid increase in its use in a number of European countries and at the European Union (EU) level. European governments often undertake tasks that would be done by private companies in the United States, such as the provision of transport, energy, water and waste management, health services, etc. In the United States the focus of BCA has often been regulatory impact analysis, rather than public project evaluation. One might, therefore, expect that Europeans might approach some things differently from their American counterparts and that new insights might result from these efforts. The articles in this symposium, taken from the recent European Society for Benefit-Cost Analysis (SBCA) conference in Toulouse, illustrate some of these differences and some converging themes.